Lip carcinoma mimicking keratoacanthoma: case reports - Luciano Henrique Ferreira LIMA; Ana Paula Cota VIANA; Giovanna Ribeiro SOUTO; Soraya de Mattos Camargo GROSSMANN; Carlos Roberto MARTINS; Hermínia Marques CAPISTRANO (Faculdade São Leopoldo Mandic, 2022)
ABSTRACT Oral amyloidosis is a disease characterized by extracellular and irreversible deposition of amorphous and fibrillar proteins in the oral cavity, being strongly associated with Multiple Myeloma. The objective of this study is to report a case of a 62-year-old woman diagnosed with Multiple Myeloma who, approximately 2 years after starting treatment for the underlying disease, presented a lesion on the lateral border of the tongue with exophytic growth, pinkish color, vascularized, painless, measuring 3cm in its largest diameter. After histopathological analysis through incisional biopsy, a final diagnosis of amyloidosis was obtained. As a local treatment, we opted for complete excision of the lesion. The patient evolved to death due to Multiple Myeloma influenced by the diagnosis of systemic amyloidosis. Oral amyloidosis is usually associated with the systemic presentation of the disease, making it necessary to conduct a thorough investigation of other organs. Its diagnosis is important since the prognosis is directly related and can negatively influence survival rates and treatment of the underlying disease.